2019
DOI: 10.1038/s41467-019-11034-x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 100 THz-spanning ultraviolet frequency combs in a non-centrosymmetric crystalline waveguide

Abstract: Ultraviolet frequency combs enable applications ranging from precision spectroscopy to atomic clocks by addressing electronic transitions of atoms and molecules. Access to ultraviolet light via integrated nonlinear optics is usually hampered by the strong material dispersion and large waveguide attention in ultraviolet regions. Here we demonstrate a simple route to chip-scale ultraviolet comb generators, simultaneously showing a gap-free frequency span of 128 terahertz and high conversion efficiency. This proc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…Despite the successful demonstration of high Q resonators on AlN, the large chromatic dispersion and group velocity dispersion in the UV and Vis spectra remain to be the significant challenges towards realizing highly efficient frequency conversion through χ (2) or χ (3) process using AlN devices. Recently, X. Liu et al proposed a chirp-modulated taper AlN waveguide to achieve broad phase matching using a near-visible pumping wavelength [221]. By fully utilizing the χ (2) and χ (3) nonlinearities, over 100 THz of coherent frequency spanning (360-425 nm) was achieved on AlN, and the results are as shown in Figures 7a and b.…”
Section: Iii-n Materialsmentioning
confidence: 95%
See 3 more Smart Citations
“…Despite the successful demonstration of high Q resonators on AlN, the large chromatic dispersion and group velocity dispersion in the UV and Vis spectra remain to be the significant challenges towards realizing highly efficient frequency conversion through χ (2) or χ (3) process using AlN devices. Recently, X. Liu et al proposed a chirp-modulated taper AlN waveguide to achieve broad phase matching using a near-visible pumping wavelength [221]. By fully utilizing the χ (2) and χ (3) nonlinearities, over 100 THz of coherent frequency spanning (360-425 nm) was achieved on AlN, and the results are as shown in Figures 7a and b.…”
Section: Iii-n Materialsmentioning
confidence: 95%
“…Sun et al demonstrated AlN ring resonators with intrinsic Q factors greater than 70,000 [219], while T. J. Lu et al reported AlN devices with intrinsic Q values exceeding 170,000 at 638 nm [220]. In the UV spectra region, X. Liu et al demonstrated AlN devices with intrinsic Q factors of 210,000 [221]. AlGaN/AlN alloys were also theoretically proposed [222], in which the low index contrast is promising for low loss waveguiding.…”
Section: Iii-n Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, an octave-spanning SC, covering 1.124-2.4 μm, was generated in SOI ridge waveguides [38]. In order to avoid the inherent nonlinear loss encountered in silicon in the near infrared and achieve broader SC spectra, the research moved toward other platforms, such as silicon nitride [39], chalcogenide [40], silicon-germanium [41], indium gallium phosphide [42], and aluminum nitride [43]. In the context of SC generation, Guo et al [44] have reported a mid-infrared comb source from 2.5 μm to 4 μm in silicon nitride (Si 3 N 4 ) waveguides and, recently, a (400-2400)-nm supercontinuum source has been demonstrated in integrated lithium niobate waveguides [45].…”
Section: Introductionmentioning
confidence: 99%